Trust and Trustworthy Computing Third International Conference, TRUST 2010, Berlin, Germany, June 21-23, 2010, Proceedings - Acquisti, Alessandro; Smith, Sean W.; Sadeghi, Ahmad-Reza (Security and Cryptology, 2010)
This volume contains the proceedings of the Third International Conference on Trust and Trustworthy Computing (TRUST), held at the Ritz-Carlton hotel in Berlin, Germany, June 21-23, 2010. TRUST is a rapidly growing forum for research on the technical and soc- economic aspects of trustworthy infrastructures. TRUST provides an interdis- plinary forum for researchers, practitioners, and decision makers to explore new ideas and discuss experiences in building, designing, using, and understanding trustworthy computing systems. The third edition of TRUST welcomed manuscripts in two di?erent tracks: a Technical Strand and a Socio-economic Strand. We assembled an engaging program with 21 peer-reviewed technical papers and nine peer-reviewed soc- economic papers; eight keynotes from industry, academia, and government; and panel discussions on privacy and standards. In addition, this year, TRUST was co-located with four workshops: Trust in Cloud, Hardware Security, Emerging and Future Risks, and Anonymous Signatures. We would like to thank numerous individuals for their e?ort and contri- tion to the conference and for making TRUST 2010 possible: the Organizing Committee members-Nadine Palacios and Marcel Winandy-for their trem- dous help with all aspects of the organization;the Technicaland Socio-economic Program Committee members, whose names are listed on the following pages, together with the names of external reviewers who helped us in the process of selecting manuscripts to be included in the conference proceedings; the keynote and invited speakers; and the invited panel speakers.